2004
DOI: 10.1073/pnas.0400923101
|View full text |Cite
|
Sign up to set email alerts
|

A regulator that inhibits transcription by targeting an intersubunit interaction of the RNA polymerase holoenzyme

Abstract: The structures of the bacterial RNA polymerase holoenzyme have provided detailed information about the intersubunit interactions within the holoenzyme. Functional analysis indicates that one of these is critical in enabling the holoenzyme to recognize the major class of bacterial promoters. It has been suggested that this interaction, involving the flap domain of the ␤ subunit and conserved region 4 of the subunit, is a potential target for regulation. Here we provide genetic and biochemical evidence that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 27 publications
2
65
0
Order By: Relevance
“…In prior work we demonstrated that the ability of AsiA to stably associate with the RNAP holoenzyme and inhibit 70 -dependent transcription depends on the strength of the 70 region 4/␤-flap interaction (23). Thus, we showed that substitutions in 70 region 4 that weaken the 70 region 4/␤-flap interaction facilitate AsiAdependent transcription inhibition and substitutions that strengthen the 70 region 4/␤-flap interaction have the opposite effect.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In prior work we demonstrated that the ability of AsiA to stably associate with the RNAP holoenzyme and inhibit 70 -dependent transcription depends on the strength of the 70 region 4/␤-flap interaction (23). Thus, we showed that substitutions in 70 region 4 that weaken the 70 region 4/␤-flap interaction facilitate AsiAdependent transcription inhibition and substitutions that strengthen the 70 region 4/␤-flap interaction have the opposite effect.…”
Section: Discussionmentioning
confidence: 83%
“…To do this, we used either a CI-␤-flap fusion protein lacking the ␤-flap-tip helix or an ␣-70 fusion protein carrying amino acid substitution F563Y, which weakens the 70 region 4/AsiA interaction (23). We found that disrupting either the AsiA/␤-flap interaction or the 70 region 4/AsiA interaction abolished the stimulatory effect of AsiA on lacZ transcription (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An additional surprising result was finding that T7A1 DNA, heparin and RNAP came to equilibrium and reached the same final state relatively quickly, regardless of order of mixing, under the conditions of this experiment. The ability to form transcription complexes in the face of competition by heparin was lost when the σ 70 domain 4-β flap interaction was disrupted by mutations R541C/L607P (Gregory et al, 2004), and diminished when σ 70 lacked its N-terminal domain 1.1 ( Figure 6B). Thus, a parallel can be drawn between these σ 70 and gp55 promoters: sufficiently avid formation of promoter complexes to overcome the heparin competitor characterized those promoter complexes with the more extensive set of protein-protein as well as protein-DNA interactions and was sensitive to loss of these individual interactions.…”
Section: Avid Formation Of the Activated T4 Late Promoter Complexmentioning
confidence: 99%